Clonal growth forms in Arctic plants and their habitat preferences: a study from Petuniabukta, Spitsbergen - Klimešová, J. (Jitka); Doležal, J. (Jiří); Prach, K. (Karel); Košnar, J. (Polish Polar Research, 2012)
The ability to grow clonally is generally considered important for plants in Arctic regions but analyses of clonal characteristics are lacking for entire plant communities. To fill this gap, we assessed the clonal growth of 78 plant species in the Petuniabukta region, central Spitsbergen (Svalbard), and analyzed the clonal and other life-history traits in the regional flora and plant communities with respect to environmental gradients. We distinguished five categories of clonal growth organs: perennial main roots produced by non-clonal plants, epigeogenous rhizomes, hypogeogenous rhizomes, bulbils, and stolons. Clonal growth differed among communities of the Petuniabukta region: non-clonal plants prevailed in open, early-successional communities, but clonal plants prevailed in wetlands.